2020
DOI: 10.3390/polym12081823
|View full text |Cite
|
Sign up to set email alerts
|

Straight Versus Branched Chain Substituents in 4′-(Butoxyphenyl)-3,2′:6′,3″-terpyridines: Effects on (4,4) Coordination Network Assemblies

Abstract: The preparation and characterization of the isomers rac-4′-(4-butan-2-yloxyphenyl)-3,2′:6′,3″-terpyridine (rac-2), 4′-(2-methylpropoxyphenyl)-3,2′:6′,3″-terpyridine (3) and 4′-(tert-butoxyphenyl)-3,2′:6′,3″-terpyridine (4) are reported. The compounds react with Co(NCS)2 under conditions of crystal growth at room temperature to give single crystals of [{Co(rac-2)2(NCS)2}·CHCl3]n, [Co(3)2(NCS)2]n and [{Co(4)2(NCS)2}·CHCl3]n which possess (4,4) networks, with the Co centers acting as 4-connecting nodes. Powder X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We have also investigated the effects of the length of the alkyl chain in [CoL2(NCS)2]n 2Dnetworks in which L is a 4'-(4-n-alkyloxyphenyl)-3,2':6',3"-terpyridine, and have demonstrated that an increase in the n-alkyloxy chain length results in a change in the conformation of the 3,2':6',3"-tpy metal-binding domain [10]. This investigation was extended to isomeric C4-alkyloxy substituents, and revealed significant structural perturbation on going from n-butyl to branched isomers, but only subtle changes across the series rac-4-butan-2-yl, 2-methylpropyl and tert-butyl peripheral groups [21]. We have also investigated the effects of introducing different halogen-substituents in 3,2':6',3"-tpy and 4,2':6',4"-tpy ligands containing 4'-biphenyl-4-yl substituents [12,22].…”
Section: Introductionmentioning
confidence: 92%
“…We have also investigated the effects of the length of the alkyl chain in [CoL2(NCS)2]n 2Dnetworks in which L is a 4'-(4-n-alkyloxyphenyl)-3,2':6',3"-terpyridine, and have demonstrated that an increase in the n-alkyloxy chain length results in a change in the conformation of the 3,2':6',3"-tpy metal-binding domain [10]. This investigation was extended to isomeric C4-alkyloxy substituents, and revealed significant structural perturbation on going from n-butyl to branched isomers, but only subtle changes across the series rac-4-butan-2-yl, 2-methylpropyl and tert-butyl peripheral groups [21]. We have also investigated the effects of introducing different halogen-substituents in 3,2':6',3"-tpy and 4,2':6',4"-tpy ligands containing 4'-biphenyl-4-yl substituents [12,22].…”
Section: Introductionmentioning
confidence: 92%
“…Our recent investigations into the formation of (4,4) nets assembled from 3,2 :6 ,3 -tpy ligands and Co(NCS) 2 illustrated both the conformational flexibility of the 3,2 :6 ,3 -tpy unit (Scheme 1) and the effects of introducing different alkyloxy substituents in the 4 -position of the 3,2 :6 ,3 -tpy ligand [17][18][19]. We also noted the role that different lattice solvents play in assemblies arising from a combination of Co(NCS) 2 and 4 -{4-(naphthalen-1-yl)phenyl}-3,2 :6 ,3 -terpyridine [20].…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 2 illustrates the three possible planar conformations of 3,2 :6 ,3 -tpy. We have recently demonstrated conformational switching in free 4 -(4-n-alkyloxyphenyl)-3,2 :6 ,3 -terpyridines [12], and in [Cu 2 (µ-OAc) 4 L] n 1D-chains [13] and [Co(NCS) 2 L 2 ] n 2D-networks where L is a 4 -(4-n-alkyloxyphenyl)-3,2 :6 ,3 -tpy [14,15] as a function of the alkyloxy chain length. In these structures, the 3,2 :6 ,3 -tpy domain adopts either conformation I or II (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%